Analysis of Character Dynamics and Educational Values in the 2025 Animated Film Jumbo - Anggraini, Zuniar Nadhiva (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Animated films are often considered a risk-free form of entertainment for children. However, not all animated films provide entirely child-friendly content. The film Jumbo (2025) is an example of animation that includes elements of bullying and verbal abuse, which has sparked various public reactions. This study aims to analyze the film’s psychological impact on children by using a literary psychology approach based on Sigmund Freud’s psychoanalytic theory, particularly the concepts of the id, ego, and superego. The method used in this research is library research and descriptive analysis of crucial moments in the film, along with public responses on social media platforms. The findings indicate that while the film conveys positive messages such as courage and empathy, the depiction of violence without adult guidance may affect children’s moral development, reinforcing the dominance of the id and weakening the control of the superego. Public responses on social media vary, suggesting that cultural and social contexts contribute significantly to how violence in media is perceived. Therefore, it is essential for parents to be actively involved when their children watch such films. Further research is also needed to explore the impact of visual media on children’s emotional and social development.